A Peran Notaris Dalam Mendukung Investasi Di Era Masyarakat Ekonomi ASEAN (MEA) - Utami, Ni Putu Mirayanthi (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 1 (2020)DO - 10.24843/AC.2020.v05.i01.p03, 2020)
Indonesia is one of the ASEAN members who agreed to implement the ACIA which focuses on investment, as the result of the implementation of the AEC. With the expectation of increasing foreign investment activities between ASEAN member countries and becoming one of the investment destinations in the world. It is proven that Indonesia still the choice of foreign investors. In order to support interests of foreign investors in conducting their business, so the role of the Notary public in investment activities needed through written proof. This study aims to analyse and provide an understanding of the role of the Notary in supporting investment in Indonesia when the AEC is implemented. This research using normative juridical methods. The study results show that the role of the Notary through direct investment is authorized to make authentic deeds based on Company Law. Furthermore, the authority of the Notary is regulated in Notary Law and Notary Law Amandement such as: providing legal counselling, services and legalizing public documents that will be used in Indonesia or needed for investment abroad. The implication of AEC it would be awared by the Notary. Therefore as a profession in a field of law, the have a to provide a social services by mastering in English and knowledge able in investment of law accordance with hierarchy of legislation and increasing competence following Notary Law and Notary Law Amandement, Notary Ethics Code, and Bylaws I.N.I. so that they can compete professionally. Indonesia merupakan salah satu anggota ASEAN yang menyetujui direalisasikannya ACIA yang berfokus pada investasi, sebagai implikasi diberlakukannya MEA. Dengan harapan dapat meningkatkan kegiatan investasi asing antara negara-negara anggota ASEAN dan menjadi salah satu tujuan investasi di dunia. Terbukti Indonesia masih menjadi pilihan investor asing. Guna menunjang kepentingan investor dalam menjalankan usahanya, maka peranan Notaris dalam kegiatan investasi sangat dibutuhkan melalui pembuktian tertulis. Studi ini bertujuan untuk menganalisa dan memberikan pemahaman peranan Notaris dalam mendukung investasi di Indonesia saat MEA diberlakukan. Penelitian menggunakan metode yuridis normatif. Hasil studi menunjukkan bahwa peran Notaris melalui investasi langsung yaitu berwenang membuat akta otentik yang dilandasi dengan Undang-Undang Perseroan Terbatas. Selain itu, kewenangan Notaris diatur dalam Undang-Undang Jabatan Notaris dan Undang-Undang Jabatan Notaris Perubahan seperti: memberikan penyuluhan hukum, pelayanan dan melegalisasi dokumen publik yang akan digunakan di Indonesia atau diperlukan untuk investasi di luar negeri. Implikasi diberlakukannya MEA juga harus disadari oleh Notaris. Maka sebagai profesi hukum dalam memberikan pelayanan kepada masyarakat haruslah berbekal penguasaan Bahasa Inggris, penguasaan mengenai hukum investasi sesuai dengan hirarki perundang-undangan dan peningkatan kompetensi sesuai dengan Undang-Undang Jabatan Notaris dan Undang-Undang Jabatan Notaris Perubahan, Kode Etik Notaris, dan Anggaran Rumah Tangga I.N.I sehingga mampu bersaing secara profesionalitas.